Application of Artificial Intelligence in Quality Test of Vibrating Fruit Harvesting Mechanical Operation. Issue 1 (January 2020) - Yang, Xiaozhou
Abstract: Harvesting operations were an important part of the production of fruit. In order to improve the efficiency of harvesting fruit and reduce the cost of harvesting, in view of the small working space in the dwarf dense planting mode of China's orchard, the artificial intelligence technology was applied to vibrating fruit harvesting mechanical operation, and the theoretical analysis of artificial intelligence technology application was analyzed; The equipment requirements of artificial intelligence in vibrating fruit harvesting machenical operation were studied. On this basis, the system application process of artificial intelligence in the harvesting machenical operation of fruit trees was deeply explored, and the work was carried out in the practice of mechanical operation, and the recovery rate was detected to be 90% to 95%. Tests had shown that the recovery rate was 36% higher than the traditional vibrating fruit harvesting technology.